The social harmony of local religious groups - Sulistyani, Hapsari Dwiningtyas; Rahardjo, Turnomo; Rahmiaji, Lintang Ratri (Universitas Negeri Yogyakarta, 2020)
As a multicultural nation, minority groups are embedded in the discourse of nationality and social harmony in Indonesia. The term social harmony signifies that each race, ethnicity, or religion must be placed in an equal standing/position. The research focuses on understanding the identity negotiation strategies, in establishing the social harmony, that are used by adherents of local religions which are considered minorities in a community where the majority of people believe in formal religions. This study uses the Co-Cultural Theory and employs a phenomenology research method to explores the way in which co-cultural groups' members negotiate their cultural differences with the members of dominant groups. The groups that are chosen as the subject of this research are the religious groups that live in a relatively supportive community (Kawruh Jiwa) and the group that has experienced numerous clashes with other groups in the region (Sapta Darma). The result of the research indicates that communication strategies used by local religious believer groups in establishing social harmony are: educating others, self-censoring, and bargaining. Those three communication strategies create different co-cultural positions. Educating others creates an accommodation position, self-censoring produces surface assimilation, and bargaining strategy generates a situation where marginal groups are in a partial separation.Sebagai negara multikultural, kelompok minoritas berada dalam wacana kebangsaan dan keharmonisan sosial di Indonesia. Istilah harmoni sosial menandakan bahwa setiap ras, etnis, atau agama harus ditempatkan dalam posisi/kedudukan yang sama. Penelitian berfokus pada pemahaman strategi negosiasi identitas, dalam membangun sosial harmoni, yang digunakan oleh penganut agama lokal yang dianggap minoritas dalam sebuah komunitas di mana mayoritas orang percaya pada agama formal. Penelitian ini menggunakan teori co-cultural dan menggunakan metode penelitian fenomenologi untuk mengeksplorasi cara anggota kelompok budaya yang berbeda menegosiasikan perbedaan budaya mereka dengan anggota kelompok dominan. Kelompok-kelompok yang dipilih sebagai subjek penelitian ini adalah kelompok agama yang hidup dalam komunitas yang relatif mendukung (Kawruh Jiwa) dan kelompok yang telah mengalami banyak bentrokan dengan kelompok lain di wilayah tersebut (Sapta Dharma). Hasil penelitian menunjukkan bahwa strategi komunikasi yang digunakan oleh kelompok penganut agama setempat dalam membangun kerukunan sosial adalah: mendidik yang lain, menyensor diri sendiri, dan tawar menawar. Ketiga strategi komunikasi itu tercipta posisi co-cultural yang berbeda. Mendidik orang lain menciptakan posisi akomodasi, swasensor menghasilkan asimilasi permukaan, dan strategi perundingan menghasilkan situasi di mana kelompok marginal berada dalam pemisahan parsial.